Design and fabricate the smart rack shoes - Nor Fadilah, Yah (2010)
This project is deal with the generating a new idea to produce a smart rack shoes which can be foldable and multifunction usage. The objective of this project is to design and fabricate the smart rack shoes. Some review has been through the internet and domestic area about the using and what they need in a rack shoes. Based on the research, most of the previous product is in a rigid position. Then, there are no product which providing the space or storage for a stuff like umbrella. Nowadays, users like to search a portable product and just buying a product, but it can be used for many functions. In other words, the multifunction or multipurpose product is more selected compared to the product in single function only. In order to improve the function of the existing product, a smart rack shoes with two functions is designed. This product offered the function to place the shoes and hung or holds the umbrella. Therefore, the user no need to place their umbrella under the stairs, or hung them at the wall.